The Effect of Price, Public Purchasing Power And Consumption Level on Rice Commodity Inflation in Pangkalpinang City - Rustarto, Arif; Ali, Hapzi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The purpose of this study is to analyze the effect of price, purchasing power and consumption level on rice commodity inflation in Pangkalpinang City. Rice is a staple food in Indonesia, including in Pangkalpinang, so weakening prices and purchasing power can significantly affect consumption and inflation levels. The method in this study uses a quantitative method with secondary data sourced from the Central Statistics Agency (BPS) and other related agencies in Pangkalpinang City. Data analysis in this study uses regression analysis which aims to determine the relationship between price variables, purchasing power, consumption and inflation. The results of the study indicate that there is a significant influence between rice prices and people's purchasing power on rice consumption levels and inflation in Pangkalpinang. The results of this study are expected to be a reference for local governments and related parties in formulating effective policies to maintain price stability and public welfare, as well as mitigating the negative impacts of inflation.